Zinc oxide nanoparticles application alleviates salinity stress by modulating plant growth, biochemical attributes and nutrient homeostasis in Phaseolus vulgaris L - Gupta, Aayushi; Bharati, Rohit; Kubes, Jan; Popelkova, Daniela; Praus, Lukas; Yang, Xinghong; Severova, Lucie; Skalicky, Milan; Brestic, Marian (Frontiers in Plant Science, 2024)
Salt stress poses a significant challenge to global agriculture, adversely affecting crop yield and food production. The current study investigates the potential of Zinc Oxide (ZnO) nanoparticles (NPs) in mitigating salt stress in common beans. Salt-stressed bean plants were treated with varying concentrations of NPs (25 mg/L, 50 mg/L, 100 mg/L, 200 mg/L) using three different application methods: foliar application, nano priming, and soil application. Results indicated a pronounced impact of salinity stress on bean plants, evidenced by a reduction in fresh weight (24%), relative water content (27%), plant height (33%), chlorophyll content (37%), increased proline (over 100%), sodium accumulation, and antioxidant enzyme activity. Application of ZnO NPs reduced salt stress by promoting physiological growth parameters. The NPs facilitated enhanced plant growth and reduced reactive oxygen species (ROS) generation by regulating plant nutrient homeostasis and chlorophyll fluorescence activity. All the tested application methods effectively mitigate salt stress, with nano-priming emerging as the most effective approach, yielding results comparable to control plants for the tested parameters. This study provides the first evidence that ZnO NPs can effectively mitigate salt stress in bean plants, highlighting their potential to address salinity-induced growth inhibition in crops.